The Fixed Stars : Thirty-Seven Emblems for the Perilous Season. - Conn, Brian (University of Alabama Press, 2010)
Juxtaposing barbarity and whimsy, Brian Conn's The Fixed Stars is a novel that has the tenor of a contemporary fable with nearly the same dreamlike logic. At the novel's heart are the John's Day celebration and the interactions of a small community dealing with a mystery disease. Routinely citizens are quarantined and then reintegrated into society in rituals marked by a haunting brutality. The infected and the healthy alike are quarantined. In a culture that has retreated from urbanism into a more pastoral society, the woman who nurtures spiders and the man who spins hemp exist alongside the.